Europarties after enlargement : organization, ideology and competition - Bressanelli, Edoardo; SpringerLink (Online service). (London : Palgrave Macmillan UK, 2014)
By comparing the importance of representative democracy to the EU as enshrined in the Lisbon Treaty with the political systems in the EU's newest member states, this study explores whether representative democracy can really exist in an enlarged EU and explores the constraints and opportunities for political parties operating the in the EU.
Keywords: Political science; Comparative politics; Democracy; Elections; European Union; Russia -- Politics and government; Political Science and International Relations; Russian and Post-Soviet Politics; Electoral Politics